Positivity and growth - Richards, Joel; Perry, Rachel (Ascent Audio, 2024)
Cultivating a positive outlook can help you and your team embrace strengths, see opportunities instead of problems, and even feel more engaged in routine tasks. This book provides insights on how to create an environment where everyone can flourish and grow. You'll learn about the effects of emotional contagion; how gratitude, feedback, and perspective matter; and how to establish an optimistic and innovative team culture.
Online resource; title from title details screen (O'Reilly, viewed December 10, 2024)
Keywords: Emotions in the workplace; Optimism; Leadership; Optimisme; Audiobooks; Livres audio